Caesarius of Arles: the making of a Christian community in late antique Gaul - Klingshirn, William E. (Cambridge studies in medieval life and thought, 1994)
This book studies the processes by which the pagan Roman empire was transformed into the Christian middle ages. Drawing on the perspectives of social history, archaeology and anthropology, it focuses on the strategies of Bishop Caesarius of Arles (AD 470–542) to promote Christian values, practices and beliefs among the pagans, Jews and Christians of southern France, and on the resistance provoked by his efforts among the population. This is the first book in English about Caesarius, and the only book to discuss southern Gaul during the sixth century. It examines afresh the crucial years of continuity, disruption, and profound change which followed the end of the Roman empire in the west, and the effects of Caesarius' programme under the later Merovingians and Carolingians.